Rapid Generation of Amyloid from Native Proteins In vitro - Dorta-Estremera, Stephanie M (MyJove Corporation, 2013)
Proteins carry out crucial tasks in organisms by exerting functions elicited from their specific three dimensional folds. Although the native structures of polypeptides fulfill many purposes, it is now recognized that most proteins can adopt an alternative assembly of beta-sheet rich amyloid. Insoluble amyloid fibrils are initially associated with multiple human ailments, but they are increasingly shown as functional players participating in various important cellular processes. In addition, amyloid deposited in patient tissues contains nonproteinaceous components, such as nucleic acids and glycosaminoglycans (GAGs). These cofactors can facilitate the formation of amyloid, resulting in the generation of different types of insoluble precipitates. By taking advantage of our understanding how proteins misfold via an intermediate stage of soluble amyloid precursor, we have devised a method to convert native proteins to amyloid fibrils in vitro. This approach allows one to prepare amyloid in large quantities, examine the properties of amyloid generated from specific proteins, and evaluate the structural changes accompanying the conversion.